2013
DOI: 10.1152/ajprenal.00129.2013
|View full text |Cite
|
Sign up to set email alerts
|

Real-time electrochemical detection of ATP and H2O2release in freshly isolated kidneys

Abstract: Extracellular nucleotides such as adenosine-5'-triphosphate (ATP) and reactive oxygen species are essential local signaling molecules in the kidney. However, measurements of changes in the interstitial concentrations of these substances in response to various stimuli remain hindered due to limitations of existing experimental techniques. The goal of this study was to develop a novel approach suitable for real-time measurements of ATP and H₂O₂ levels in freshly isolated rat kidney. Rats were anesthetized and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Relative (150). These studies not only confirmed that H 2 O 2 levels were increased in SS rats fed a high-salt diet compared with low salt but also that medullary H 2 O 2 levels were significantly higher than in the cortex.…”
Section: Medullary O 2 ·ϫ No and H 2 O 2 As Determinants Of Blood supporting
confidence: 66%
“…Relative (150). These studies not only confirmed that H 2 O 2 levels were increased in SS rats fed a high-salt diet compared with low salt but also that medullary H 2 O 2 levels were significantly higher than in the cortex.…”
Section: Medullary O 2 ·ϫ No and H 2 O 2 As Determinants Of Blood supporting
confidence: 66%
“…Nucleotide release from renal epithelia is both constitutive (suggestive of a 'purinergic tone') and activated by mechanical or agonistinduced stimuli. Microelectrodes have measured steady-state ATP concentrations of~400 nM in the rat kidney cortex and showed that infusion of Ang II caused a rapid and transient increase, consistent with regulated release of nucleotide [277].…”
Section: Release and Metabolism Of Nucleotidesmentioning
confidence: 92%
“…To test the contribution of NOX4 to H 2 O 2 release in glomeruli, we employed here a novel approach featuring enzymatic biosensors capable of detecting specific substances and dynamic changes in their concentrations in fresh tissues. 32,33 In order to test H 2 O 2 release, we isolated glomeruli from the wild-type SS rats and age-matched SS Nox42/2 animals and washed them by spinning; next, glomeruli were placed into a 100-ml tube. A biosensor was then placed into the solution (see Figure 4A) and, after allowing time for equilibration, stable basal levels of H 2 O 2 were recorded for several minutes.…”
Section: Nox4 Is the Major Source For H 2 O 2 Production In The Ss Ramentioning
confidence: 99%